Pendampingan Pengembangan Usaha UMKM Radit Keramik melalui Program PKL: Pengabdian - Shinta Sartika Pranata; Achmad Rifqi Darmawan; Dewi Nurul Syamsiyah; Indi Nurul Insani; Mohamad Helmi Fauzan (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service project was conducted through the KPB/PKL program at UMKM Radit Keramik in Purwakarta to identify the main issues faced by the business and provide improvement recommendations. The aim of this activity was to assist the MSME in overcoming limited marketing reach, unstructured financial management, and minimal product innovation. The methods applied included observation, interviews, mentoring, and business analysis. The program resulted in digital marketing development, business legality support, financial recording recommendations, and product innovation ideas. This program is expected to strengthen business management, expand market access, and support the sustainability of Radit Keramik.